2015
DOI: 10.1111/bju.13232
|View full text |Cite
|
Sign up to set email alerts
|

Trends in incidence and survival for upper tract urothelial cancer (UTUC) in the state of Victoria – Australia

Abstract: ObjectiveTo investigate the incidence and mortality trends of upper tract urothelial cancers (UTUC) in Victoria over the last decade. Patients and MethodsAge-adjusted incidence and mortality rates were calculated for UTUC. These were identified using data from the Victorian Cancer Registry from 2001 until 2011 based on histological diagnoses. Age at diagnosis, sex and demographical location were compared. ResultsThe age-standardised incidence of UTUC remained stable from 2001 to 2011. There were 278 deaths fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…This is in line with reported findings in other countries. An Australian population-based study including 722 patients described a stable 5-year relative survival of 30% (2001)(2002)(2003)(2004)(2005)(2006) and 36% (2007-2011) [16]. A nationwide study from the UK, which included patients diagnosed between 1985 and 2010, showed a decline in the 5-year relative survival from 60% to 48% [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with reported findings in other countries. An Australian population-based study including 722 patients described a stable 5-year relative survival of 30% (2001)(2002)(2003)(2004)(2005)(2006) and 36% (2007-2011) [16]. A nationwide study from the UK, which included patients diagnosed between 1985 and 2010, showed a decline in the 5-year relative survival from 60% to 48% [20].…”
Section: Discussionmentioning
confidence: 99%
“…The literature on the incidence of UTUC is sparse, and studies are often not population‐based and mostly reflect different time periods, which hampers adequate comparison with the results of the present study. An Australian study reported a stable age‐standardized incidence rate between 2001 and 2011 [ 16 ]. Another study from Australia confirmed this observation and also did not find an increase in incidence for the period 1977–2003 [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen studies compared UTUC incidence based on calendar time [ 15 18 , 22 , 25 28 , 34 , 39 47 ]. For three of these studies, more accurate numbers were obtained by contacting the study authors.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Kockelbergh and colleagues [ 15 ] studied the National Cancer Registration and Analysis Service (NCRAS)—which contains data from the NCDR—from 2001 to 2013 and reported a similar overall increase in incidence throughout time. The third study with accurate numbers obtained from the study authors was by Woodford and colleagues [ 18 ], who studied the Victorian Cancer Registry of Australia from 2001 to 2011 and found the incidence of UTUC to be stable throughout time.…”
Section: Resultsmentioning
confidence: 99%
“…First, UTUC has a relatively low incidence rate, but it is aggressive and affected patients have a relatively poor prognosis. [41] It is possible that E-cadherin may not stand out because patients with UTUC have a poor prognosis due to the strong aggressiveness of the carcinoma. Second, distinct genetic profiles or molecular biology between upper and lower urinary tract tumors may affect the results.…”
Section: Discussionmentioning
confidence: 99%